Homoeroticism in the biblical world : a historical perspective - Nissinen, Martti (Minneapolis (Minn.): Fortress, 1998)
Surveys attitudes in the ancient world toward homoeroticism, that is, erotic same-sex relations, focusing on the Bible and its cultural environment -- Mesopotamia, Greece, Rome, Israel. Homoeroticism is examined as a part of gender identity, i.e., the interplay of sexual orientation, gender identification, gender roles, and sexual practice. In the patriarchal cultures of the biblical world, Nissinen shows, homoerotic practices were regarded as a role construction between the active and passive partners rather than as expressions of an orientation moderns call "homosexuality." Nissinen shows how this applies to the limited acceptance of homoerotic relationships in Greek and Roman culture, as well as to Israel's and the early church's condemnation of any same-sex erotic activity. (Augsburg Fortress)
Keywords: Bible and homosexuality; Homosexuality in the Bible; Homosexuality -- History -- To 1500